2010
DOI: 10.1007/s12529-010-9132-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of Depression and Suicidal Ideation with Unreasonable Patient Demands and Complaints Among Japanese Physicians: A National Cross-sectional Survey

Abstract: Physicians should recognize the health risks of unreasonable demands and complaints, and hospitals should provide support for physicians dealing with these stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
34
2
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 47 publications
(41 citation statements)
references
References 19 publications
1
34
2
2
Order By: Relevance
“…For example, the prevalence of depressive symptoms among physicians in the US, Britain (intensive care unit physicians), Canada, Norway, Japan, and Benin were 11.3%, 12%, 15.5%, 11%, 8.8%, and 14%, respectively [9][14]. The relatively poor mental health status among physicians in China may be attributed to various reasons.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the prevalence of depressive symptoms among physicians in the US, Britain (intensive care unit physicians), Canada, Norway, Japan, and Benin were 11.3%, 12%, 15.5%, 11%, 8.8%, and 14%, respectively [9][14]. The relatively poor mental health status among physicians in China may be attributed to various reasons.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies indicated that the prevalence of depressive symptoms among physicians ranged from 10% to 15% in the US, Britain, Norway, and Japan [9][14]. A recent Dutch investigation concluded that anxiety and depressive symptoms were prevalent in 24% and 29% of physicians, respectively [15].…”
Section: Introductionmentioning
confidence: 99%
“…Wall et al [22] demonstrated a cross-sectional association between interpersonal conflicts such as Brecent degrading experiences^or Bharassment at work^and the risk of suicidal ideation among a total of 421 Italian and Swedish doctors. In Japan, Wada et al [31] conducted a cross-sectional study with 3862 doctors and found a significant association between interpersonal conflicts (unreasonable patient demands and complaints) reported in the previous 6 months and their suicidal ideation. Our results also presented that interpersonal conflict had higher levels of OR with the risk of suicidal ideation in both genders.…”
Section: Discussionmentioning
confidence: 99%
“…OPEN ACCESS association of depressive symptoms with dietary habits. We adjusted for age, working factors which were associated with depressive symptoms in previous studies [1,6] such as the number of overnight works, on-calls, and off-duties, average hour of sleeping not doing overnight work, and unreasonable violence at work. We also adjusted for lifestyle factors such as smoking, alcohol intake, and regular exercise.…”
Section: Methodsmentioning
confidence: 99%